Stegodon SEA-crossing: Swim, shrink, and disperse - Christine Hertler; Alexandra A.E. van der Geer; Mika Rizki Puspaningrum; Jan-Olaf Reschke; Iwan Pramesti Anwar; Ericson Hölzchen (Earth History and Biodiversity)
Dispersal of terrestrial mammals into Wallacea requires the crossing of sea straits. Stegodons, an extinct family of proboscideans, managed to settle on roughly a dozen Wallacean islands during the Pleistocene. Their distribution pattern is, however, not well understood. It results from the interaction of two specific processes, namely respective swimming performances on the one hand, as well as island dwarfing on the other. Reduction of body mass has an impact on swimming performance, because smaller size leads to a slower swimming speed and lower deposits of available energy. In this study we conducted a series of experiments with the agent-based model SEAcross, designed to monitor swimming performances of terrestrial mammals across sea straits by measuring crossing success rates (CSR). We found that the dispersal pattern is in accordance with size-dependent swimming performances, geographic width as well as current speed and direction. Because currents change on a seasonal scale, bottlenecks decelerating or even preventing dispersal are rarely absolute, but should be considered as seasonal phenomena. Our results allow for an in-depth analysis of dispersal routes and success. Dispersal performances cannot, however, explain the lack of a fossil record of stegodons in the eastern part of Wallacea. With very few exceptions, routes should be manageable for terrestrial mammals with the size of a stegodon. Our results illustrate, however, the usefulness and applicability of agent-based models in order to further examine geographic dispersal barriers in conjunction with the dynamics of animal behavior.